Recurrent impending thyroid storm in a girl with Graves’ disease: a case report - Novina, Novina; Putri, Nisa Hermina; Pramudani, Nadia; Faisal, Faisal (Indonesian Pediatric Society, 2023)
Thyroid storm is an acute, life-threatening, hypermetabolic state in children with thyrotoxicosis. Before the thyroid storm occurs, the patient falls into a “warning stage” called impending thyroid storm. Rapid diagnosis and prompt treatment of an impending thyroid storm are crucial to prevent further life-threatening impacts. We describe a pediatric patient who experienced two episodes of impending thyroid storm with negative COVID-19 tests during the COVID-19 pandemic.